The Movielike Nature of Czesław Miłosz’s Poetic Language - Kaźmierczyk, Zbigniew (Porównania, 2021)
The paper develops the thesis on the movielike nature of Czesław Miłosz’s early poetry. It includes the premises of the thesis in contrast to innovative currents of the epoch. The paper discusses applying terms from the language of film as adequate when compared to the Nobel Prize winner’s synecdochic technique of imaging which is shown as the structural algorithm of the world of poetic multivoiceness. The paper displays the relation between ethics, philosophy and theology with the imaging of a poem. It proves that the advancement of the synecdochic-film technique, from figurativeness to the fluency of a take, is connected with balancing the Gnostic aversion of the poet towards the reality of body and matter. The balance between the feeling of terror of existence and its affirmation was favourable for creating fluent series: partes pro toto derived from the coming together of a name and a respected item, as well as accepting beings which are transcendent in their nature. The author of the paper states that through comparing the language of poetry and the language of film it was possible to show the poetic nature of Miłosz’s poems.